Affinity Maturation of Macrocyclic Peptide Modulators of Lys48‐Linked Diubiquitin by a Twofold Strategy. Issue 36 (8th June 2020) - Huang, Yichao; Nawatha, Mickal; Livneh, Ido; Rogers, Joseph M.; Sun, Hao; Singh, Sumeet K.; Ciechanover, Aaron; Brik, Ashraf; Suga, Hiroaki
Abstract: Messenger RNA display of peptides containing non‐proteinogenic amino acids, referred to as RaPID system, has become one of the leading methods to express libraries consisting of more than trillion‐members of macrocyclic peptides, which allows for discovering de novo bioactive ligands. Ideal macrocyclic peptides should have dissociation constants ( K D ) as low as single‐digit values in the nanomolar range towards a specific target of interest. Here, a twofold strategy to discover optimized macrocyclic peptides within this affinity regime is described. First, benzyl thioether cyclized peptide libraries were explored to identify tight binding hits. To obtain more insights into critical sequence information, sequence alignment was applied to guide rational mutagenesis for the improvement of their binding affinity. Using this twofold strategy, benzyl thioether macrocyclic peptide binders against Lys48‐linked ubiquitin dimer (K48‐Ub2) were successfully obtained that display K D values in the range 0.3–1.2 nm, which indicate binding two orders of magnitude stronger than those of macrocyclic peptides recently reported. Most importantly, this macrocyclic peptide also showed an improved cellular inhibition of the K48‐Ub2 recognition by deubiquitinating enzymes and the 26S proteasome, resulting in the promotion of apoptosis in cancer cells. Abstract : Strong binding : Benzyl thioether macrocyclic peptide binders towards Lys48‐linked ubiquitin dimer (K48‐Ub2) were successfully obtained that display K D values in the range 0.3–1.2 nm, which indicate a binding two orders of magnitude stronger than that of macrocyclic peptides recently reported.